2016
DOI: 10.1080/02827581.2016.1227472
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the future use of forests: perceptions from non-industrial private forest owners in Finland

Abstract: 9The transformation of the forest sector towards a bioeconomy calls for finding new sources of 10 competitive advantage for the whole sector to retain its future viability. Non-industrial private 11 forest (NIPF) owners are an important group of actors in the Finnish forest-based sector, as they 12 supply 80% of industrial roundwood and control numerous other tangible and intangible forest-13 based ecosystem services. Our study analyzes forest owner views on the future use of forests 14in Finland, their percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
(38 reference statements)
0
13
0
2
Order By: Relevance
“…Takala et al (2017b) found discourses that challenge the timber production and ethos of good forest management among forest owners. Häyrinen et al (2017) reported forest owners being frustrated with the services only focusing on intensive timber production. The legitimacy of clear cuttings has been loudly questioned both by forest owners and by the wider society (Valkeapää 2014;Hölttä et al 2018).…”
Section: The Road Ahead -How To Respond To Societal Changes?mentioning
confidence: 99%
See 2 more Smart Citations
“…Takala et al (2017b) found discourses that challenge the timber production and ethos of good forest management among forest owners. Häyrinen et al (2017) reported forest owners being frustrated with the services only focusing on intensive timber production. The legitimacy of clear cuttings has been loudly questioned both by forest owners and by the wider society (Valkeapää 2014;Hölttä et al 2018).…”
Section: The Road Ahead -How To Respond To Societal Changes?mentioning
confidence: 99%
“…To maintain the social acceptability of forest utilisation for timber production and to enable the involvement of forest owners with multiple objectives in timber sales, the multiple-use principle of forests should materialise from political rhetoric into action (Takala et al 2017a). The future viability of the forest sector has been connected to the ability to fulfil the expectations concerning multi-objective forest uses (Häyrinen et al 2017). As current forest practices called multi-objective forestry have not been capable of halting the loss of biodiversity in production forests, the credibility of the sustainability of Finnish forestry has been questioned.…”
Section: The Road Ahead -How To Respond To Societal Changes?mentioning
confidence: 99%
See 1 more Smart Citation
“…Joint action or organisation of forest owners has long been proposed as a remedy to the hindrances related to fragmented or small-scale forest ownership. Forest owners' associations are a heterogeneous type of organisation, but have various common objectives, including increased forest owners political power (Mattila and Roos, 2014;Sarvasova et al, 2015), improved market position (Häyrinen et al 2017;Kronholm 2016;Posavec et al, 2011), development of business activities (Glück et al 2010;Pollumäe et al 2016;Rauch, 2007;Schraml, 2005;Weiss et al, 2012), support for cooperation among forest owners and forest authorities (Aurenhammer et al 2018;Nonic et al 2011), and obtaining financial incentives (Jársky et al, 2014;Mendes et al, 2011;Živojinović et al, 2015).…”
Section: Common Action -In Forest Ownership Management and Interest mentioning
confidence: 99%
“…La industria forestal, especialmente en países del norte de Europa, está iniciando cambios en los modelos de negocio, a través de la integración de productos como biocombustibles (Huang et al 2010;Olesen et al, 2016), nuevos materiales de construcción basados en productos leñosos (Häyrinen et al 2017), o telas, plásticos y productos químicos basados en celulosa, lignina, resinas o ceras de origen forestal (Babu et al 2013;Sjostrom, 2013;Scarlat et al 2015) entre otros. Estas nuevas demandas podrían suponer un incremento en la movilización de biomasa y en la intensidad de manejo de los bosques europeos (Framstad et al, 2009) o la conversión de hábitats de alto valor ambiental en tierras productivas (Pedroli et al, 2013); cuyas políticas se han orientado, en las últimas dos décadas, más bien a favorecer su conservación y multifuncionalidad.…”
Section: Introductionunclassified